PS 18-16 Renal sodium handling in relation to plasma advanced glycation end products concentration in untreated subjects. (September 2016) - Huang, Qi-Fang; Li, Yan; Liu, Chang-Yuan; Wang, Ji-Guang
Abstract : Objective: previous experimental study showed that advanced glycation end products (AGEs) might enhance epithelial sodium channel in the renal cortical collecting duct cells. In the present study, we investigated renal sodium handling, as assessed by endogenous lithium clearance indexes, in relation to plasma AGEs concentration in subjects who did not take antihypertensive medication. Design and Method: The study subjects were previously never treated with or stopped antihypertensive medication for at least 2 weeks. We calculated fractional excretion of lithium and fractional distal reabsorption rate of sodium, as markers of proximal and distal sodium handling, respectively. Plasma AGEs concentration was measured by the enzyme-linked immunosorbent assay method and logarithmically transformed for statistical analysis. Results: The 1006 study participants (mean age 51.3 years) included 499 (49.6%) men and 40 (4.0%) diabetic patients. After adjustment for sex, age, body mass index, mean arterial pressure, pulse rate, current smoking and alcohol intake, plasma fasting glucose, serum triglycerides, serum total-to-high-density lipoprotein cholesterol ratio, plasma AGEs concentration (geometric mean [95% confidence interval] 13.4 [12.8 to 14.0] mg/mL) was significantly (P = 0.0007) associated with fractional lithium clearance (mean [±standard deviation] 21.7% ± 12.1%). For each 10-time increase in plasma AGEs concentration, fractional lithium clearance was 4.3% (absolute percentage change) lower. In tertile 3 of sodium urinary excretion, higher plasma AGEs concentration was also associated with lower fractional distal reabsorption rate of sodium (93.3% in tertile 3 vs. 95.1% in tertile 1 of plasma AGEs concentration, P = 0.002). Conclusions: Plasma AGEs concentration was positively associated with sodium renal reabsorption in the proximal tubule, as assessed by fractional lithium clearance. However, on the condition of high sodium intake, it was negatively associated with sodium reabsorption in the distal tubule, probably as a compensation of increased sodium intake and increased sodium reabsorption in the proximal tubule.